Prevalence of IgM and IgG antibodies to Toxoplasma gondii among blood donors in Thi-Qar governorate - Jaboory Hadi, Nuha (University of Thi-Qar Journal of Science, 2010)
Current study performed for the first time in Thi-Qar governorate to evaluate the seroprevalence of toxoplasmosis infection among blood donors This is may be causes transmission the infection to another person by blood transfusion. Detection IgM antibody in early stage of infection and IgG in latent stage of infection by using (ELISA BioCheck company kit).From the total serum samples (90) collected from healthy persons donated in the central blood banks in the city, Results show IgM and IgG antibodies seropositive was 13 (14.4%),25 (27.8%) respectively ,the higher percentage in IgM was 6(27.3%) was in age group 31-40 years and the lower percentage was 1(5.9%) in age group 41- 50 years, while IgG antibody recorded higher value 9(52.9%) in age group 41-50 years and the lower value in age group ‹ 20 years that was 3(15%).The statistical analysis results show significant difference between age group in IgM antibody and there is a significant difference between age group in IgG antibody. The aim of this study to evaluate the seroprevalence of toxoplasmosis among the healthy blood donors that may be cause transmission of infection to another peoples by blood transfusion by detection early and latent stages of infection.